Cascade dehydrative amination of glycerol to oxazoline (vol 8, pg 2954, 2018) - Pandya, R.; Mane, R.; Rode, C. V. (Catalysis Science & Technology, 2020)
Correction for `Cascade dehydrative amination of glycerol to oxazoline' by R. Pandyaet al.,Catal. Sci. Technol., 2018,8, 2954-2965, DOI: ;10.1039/C8CY00185E.